Examining the effectiveness of TASERS® at gaining citizen compliance - Somers, Logan J. (Criminal justice policy review, 2020)
Since their emergence within the field of policing, the use of conducted energy devices (CEDs) has produced a great deal of debate. However, few empirically rigorous studies have shed light on the extent to which CEDs (e.g., TASERs) are actually successful at gaining citizen compliance. As such, we examine 918 TASER cases collected from three police agencies to assess effectiveness in relation to citizen compliance. Findings demonstrate that officers generally classify the TASER as effective, but the level of effectiveness varies depending on whether it was used in probe or drive-stun mode. Multivariate regression models also identify a number of significant variables related to TASER effectiveness, including citizen (e.g., height, weight, gender, impairment) and officer (e.g., gender) characteristics. We discuss the findings in relation to those found in prior studies, as well as implications for research, policy, and practice.